Legal Protection of Holders of Land Loss Data In The City Land Office of Kendari - Bahrul Alam; Akhmad Khisni (Jurnal Akta, 2020)
The purpose of this study as follows: 1) To identify and explain the legal protection of land rights holders as a result of the loss of data in the land office Kendari. 2) To identify and explain the impact of the destruction of land records of the rights on public land in Kendari. 3) To identify and explain the legal aspects of the legal protection of land rights data recovery results.The method used by researchers is normative juridical law approach and specification in this study were included descriptive analysis. The source and type of data in this study are primary data obtained from field studies with interview BPN in Kendari.Secondary data were obtained from literature studies. Based on the results of research that legal protection to the right holder on the ground due to the loss of data in the land office are: 1) BPN only provide legal protection to the certificate of land rights have been restored archives; 2) The purpose of data recovery is providing legal protection for the land rights archives destroyed. BPN perform data recovery and ratify certificates and land books and letters Perkaban the measure under Article 18, Act No. 6 of 2010. The destruction of land records can weaken the strength of the evidence as a certificate as evidence of land rights. The impact of the destruction of land records of the rights on public land in Kendari are: 1) the destruction of land records can weaken the strength of the evidence as a certificate as evidence of land rights; 2) the impact of the destruction of land records lead to certificates of land rights before the restored data can not be used as evidence to take legal actions; 3) loss or destruction of land records will not necessarily be able to eliminate / abolish the rights to the land concerned. Legal aspects of the legal protection of land rights data recovery results are 1) a substantial aspect, 2) structural aspects, 3) cultural aspects.Keywords : Legal Protection; Rights to Land; Land.